How Men Manage Bulbar Urethral Stricture by Concealing Urinary Symptoms. (October 2015) - Whybrow, Paul; Rapley, Tim; Pickard, Robert; Hrisos, Susan
In this article, we present findings from research conducted as part of a multi-center surgical trial. Bulbar urethral stricture, a narrowing of the middle urethra, is a common cause of urinary problems in men that can have a profound impact on their lives. Semi-structured interviews were conducted with a sample of 19 men seeking treatment for urethral stricture. The findings reveal how men tend to develop routines and tactics to adapt to their symptoms and hide them from others rather than seek help. We argue that this concealment becomes an inseparable part of how the disease is managed and is an additional hidden practical and emotional burden for these men. In addition, we suggest that the patients only sought curative treatments once practices of social concealment are no longer viable.